Genetic dissection of clonal lineage relationships with hydroxytamoxifen liposomes. Issue 1 (December 2018) - Ransom, Ryan; Foster, Deshka; Salhotra, Ankit; Jones, Ruth; Marshall, Clement; Leavitt, Tripp; Murphy, Matthew; Moore, Alessandra; Blackshear, Charles; Brett, Elizabeth; Wan, Derrick; Longaker, Michael
Abstract Targeted genetic dissection of tissues to identify precise cell populations has vast biological and therapeutic applications. Here we develop an approach, through the packaging and delivery of 4-hydroxytamoxifen liposomes (LiTMX), that enables localized induction of CreERT2 recombinase in mice. Our method permits precise, in vivo, tissue-specific clonal analysis with both spatial and temporal control. This technology is effective using mice with both specific and ubiquitous Cre drivers in a variety of tissue types, under conditions of homeostasis and post-injury repair, and is highly efficient for lineage tracing and genetic analysis. This methodology is directly and immediately applicable to the developmental biology, stem cell biology and regenerative medicine, and cancer biology fields. Targeted genetic dissection of tissues can be used to identify cell populations and lineages. Here the authors develop 4-hydroxytamoxifen liposomes for the localized induction of CreERT2 .